Students’ Mathematical Representation Ability in Cooperative Learning Type of Reciprocal Peer Tutoring from Learning Style (Unnes Journal of Mathematics Education, 2023)
This study aims to analyze whether the Cooperative Learning type of Reciprocal Peer Tutoring (RPT) is effective in enhancing students' mathematical representation abilities, whether it is more effective than PBL in enhancing students' mathematical representation abilities, how learning styles influence students' mathematical representation abilities in Cooperative Learning type of RPT, and to describe the ability of mathematical representation in terms of learning styles in Cooperative Learning type of RPT. The research method used was a mixed method, and the design used was sequential explanatory. The sampling technique used was random sampling by class. The results showed that: (1) the ability of mathematical representation in the Cooperative Learning type of RPT achieved classical completeness; (2) the average mathematical representation ability in the Cooperative Learning type of RPT was higher than that of PBL; (3) the proportion of completeness of mathematical representation ability in Cooperative Learning type of RPT was higher than that of the PBL class, indicating that Cooperative Learning type of RPT is more effective in enhancing mathematical representation abilities; and (4) there is a positive influence of learning styles on students' mathematical representation ability in Cooperative Learning type of RPT. Subjects with visual learning styles are able to fulfill visual and verbal indicators and tend to be able to fulfill symbolic indicators. Subjects with auditory learning styles tend to be able to fulfill visual and symbolic indicators but tend to be less able to fulfill verbal indicators. Subjects with kinaesthetic learning styles are able to meet visual indicators.